Transcriptome analysis provides insights into the cell wall and aluminum toxicity related to rusty root syndrome of Panax ginseng - Tong, Aizi; Liu, Wei; Wang, Haijiao; Liu, Xiaoliang; Xia, Guangqing; Zhu, Junyi (Frontiers in Plant Science, 2023)
Rusty root syndrome is a common and serious disease in the process of Panax ginseng cultivation. This disease greatly decreases the production and quality of P. ginseng, and causes a severely threat to the healthy development of the ginseng industry. However, its pathogenic mechanism remains unclear. In this study, Illumina high-throughput sequencing (RNA-seq) technology was used for comparative transcriptome analysis of healthy and rusty root-affected ginseng. The roots of rusted ginseng showed 672 up-regulated genes and 526 down-regulated genes compared with the healthy ginseng roots. There were significant differences expression of genes involved in biosynthesis of secondary metabolites, plant hormone signal transduction, and plant-pathogen interaction. Further analysis showed that the cell wall synthesis and modification of ginseng has a strong response to rusty root syndrome. Furthermore, the rusted ginseng increased aluminum tolerance by inhibiting Al entering cells through external chelating Al and cell wall binding Al. The present study establishes a molecular model of the ginseng response to rusty root. Our findings provide new insights into the occurrence of rusty root syndrome, which will reveal the underlying molecular mechanisms of ginseng respond to this disease.